Study of structural changes in ZrO2 ceramics irradiated with heavy ions of Kr15+ with an energy of 147 MeV. (Physical Sciences and Technology, 2020)
This paper presents the results of a study of changes in structural characteristics, such as the degree ofcrystallinity, dislocation density, and deformation of the crystal lattice in ZrO2 ceramics as a result ofirradiation with heavy Kr15+ ions with an energy of 147 MeV. The choice of the type of irradiation ionsis due to the possibility of simulating the processes of defect formation comparable to the irradiation ofradiation-resistant materials by fragments of uranium fission. The radiation doses ranged from 5х1013 to1х1016 ion/cm2. The dependences of the change in the crystallographic parameters on the radiation dosewere established. At the same time, the maximum decrease for an irradiation dose of 1x1016 ion/cm2 was nomore than 10 %, which in turn indicates a high radiation resistance to the accumulation of defects duringlarge-dose irradiation. It was determined that the greatest change in the degree of crystallinity is observedabove a dose of 1х1015 ion/cm2. The data obtained indicate a high degree of resistance of these ceramics toradiation damage.